Kuwaiti female leaders' perspectives: the influence of culture on their leadership in organizations - Al-Suwaihel, Omaymah, author; Anderson, Sharon K., advisor; Timpson, William M., committee member; Zimmerman, Toni S., committee member; Banning, James H., committee member (Colorado State University. Libraries, 2009)
This research reveals the interactions between the Kuwaiti culture, gender, and leadership from the perspective of 5 Kuwaiti female leaders. The primary focus of the research is to contribute to the literature, currently lacking, that discusses the phenomenon of female leadership development in the State of Kuwait. Recently, the number of Kuwaiti females seeking leadership positions has been increasing in governmental and non-governmental organizations. This development has its challenges, given some of the barriers that exist relative to some aspects of Kuwaiti culture, gender roles, and people’s perceptions about female leaders. Within a qualitative design approach and narrative inquiry methodology, I interviewed 5 Kuwaiti females who shared their stories about their personal and professional experiences about the interactions between culture, gender, and leadership. The analysis and interpretation of this research uncovered two key findings: (a) the influence of Kuwaiti culture on female leadership and (b) the commitment of these female leaders to have a positive impact on their culture. The development of female leadership within Kuwait represents a collaborative effort by all the country's female leaders. As this research shows, these female leaders took advantage of every opportunity to prove their capabilities as leaders who deserve to serve effectively beside male leaders.
Department Head: Timothy Gray Davies.